Usefulness of psychoeducational intervention in chronic insomnia: an actigraphic study. (2nd January 2020) - Quintiliani, Maria Isabella; Imperatori, Claudio; Testani, Elisa; Losurdo, Anna; Tamburello, Stella; Contardi, Anna; Della Marca, Giacomo; Farina, Benedetto
Abstract: Background : Chronic Insomnia is a severe and disabling condition characterized by difficulty in initiating or maintaining sleep, waking up too early, despite adequate opportunity and circumstances for sleep. Maladaptive thoughts and dysfunctional beliefs about sleep are considered crucial factors in developing and perpetuating this disorder. Aims : The aim of the study was to explore the usefulness, in patients with chronic insomnia, of a one-session psychoeducational intervention on sleep-related maladaptive thoughts and beliefs, and on sleep perception. Methods : Thirty-eight patients with chronic insomnia were enrolled in the study and randomly assigned to receive psychoeducational intervention (PI+) or to act as controls (PI–). Patients wore an actigraph and compiled a sleep diary for 14 d. After the first 7 d, only PI+ patients received one session of psychoeducational intervention. Results : A significant reduction of sleep related preoccupations, a reduction of dysfunctional beliefs about sleep, and an improvement of subjective perception of sleep were observed in the PI+ group, but not in the PI– group. No significant modification was observed for objective total sleep time. Conclusions : Our results suggest that one-session psychoeducational intervention is associated with a decrease of sleep-related maladaptive thoughts and beliefs, and with an improvement on subjective sleep perception.